Facile synthesis of some 5-(3-substituted-thiophene)-pyrimidine derivatives and their pharmacological and computational studies - S. H. Sukanya; Talavara Venkatesh; S.J. Aditya Rao; N. Shivakumara; Muthipeedika Nibin Joy (Chimica Techno Acta)
A series of 5-(3-substituted-thiophene)-pyrimidine derivatives (3a-d) were synthesized via Knoevenagel condensation reaction in aq. ethanol using H2O2:HCl as a catalyst. Their pharmacological effects were evaluated. Analytical and spectroscopic methods confirmed the structures of the target molecules. The antibacterial activity studies revealed that compounds 3b and 3d exhibited the most effective zone of inhibition against bacterial strains E. coli and S. aureus, respectively. The in vitro cytotoxicity was carried out by MTT assay against MCF-7 cell line. The results showed excellent selectivity for all four compounds, among which the compound 3a exhibited remarkable cytotoxicity with a minimum cell viability range of 23.68 to 44.16%. The interaction of compounds with calf thymus DNA was determined using UV-absorption spectroscopy. The results confirmed that all the synthesized compounds interacted strongly with CT DNA through electrostatic or groove binding. In silico ADME-toxicology studies indicated that all the molecules under investigation are non-toxic with good oral bioavailability. The drug-likeness score indicated that they are suitable as drug-leads. In silico molecular docking the specified compound 3b bound with GlcN-6-P and P38 MAPk with a minimum binding energy of –7.9 and –6.4 kcal/mol, respectively. DFT study demonstrated that compound 3d was chemically and biologically more reactive due to less energy gap.